Révolution et migration : la route du sucre dans les Amériques - Nathalie Dessens (Caravelle)
In the late 18th century, Saint-Domingue was the richest Caribbean colony and the corner stone of French commerce. The Haitian Revolution (1791-1803) disrupted this strongly established economic domination. The present article examines the reconfiguration of the American sugar economy induced by this revolution and the role played by the Saint-Domingue refugee diaspora in this one, highlighting the importance of studying movements of people in the Greater Caribbean zone.